Lifestyle characteristics in adolescent female football players: data from the Karolinska football Injury Cohort - Anne Fältström; Eva Skillgate; Nathan Weiss; Henrik Källberg; Victor Lyberg; Markus Waldén; Martin Hägglund; Martin Asker; Ulrika Tranaeus (BMC, 2022)
Abstract Background Normative values of lifestyle characteristics in adolescent female football players may be used by clinicians and coaches to take actions because the potential important for well-being, performance on the pitch, and risk of injury. The aim was to report descriptive characteristics of lifestyle factors in adolescent female football players and potential changes over 1 year. Methods We included 419 adolescent competitive female football players from 12 clubs and 27 teams (age 14 ± 1 years, range 12-17 years) and 286 were followed over 1 year. The players completed an extensive questionnaire regarding demographics, football-related factors, and lifestyle factors including tobacco consumption, alcohol use, medicine intake, eating and sleeping habits, well-being, stress, coping, and passion. Baseline data are presented for the total cohort and separately for 4 age groups (12, 13, 14, and 15-17 years). Results 12% skipped breakfast, 8% skipped lunch and 11% used protein supplements several days per week. 16% slept less than 8 h/night, 8% had impaired sleep with daytime consequences, and 22% stated that they were tired in daily activities several days per week. 32% experienced stress some or most days/week and 24% were classified as having psychological distress. Medicine intake (23% vs. 34%), skipping breakfast or lunch several days per week (10% vs. 47% and 20 vs. 33%), tiredness (20% vs. 27%), stress (26% vs. 40%), and psychological distress (27% vs. 37%) increased significantly (P = 0.031 to < 0.001) at the 1-year follow-up. Conclusion Many adolescent female football players skip breakfast and lunch, have insufficient sleep, experience stress and are classified as having psychological distress. These factors increased over 1 year.